2020
DOI: 10.1017/s0007114520000963
|View full text |Cite
|
Sign up to set email alerts
|

Validation of saliva and urine use and sampling time on the doubly labelled water method to measure energy expenditure, body composition and water turnover in male and female cats

Abstract: Less invasive protocols are necessary to study energy expenditure (EE) of cats living in homes for expressing their normal living conditions. The present study compared sampling times and the use of saliva, urine and blood to measure 2H and 18O to apply the doubly labelled water method. In the first study, four cats were used to evaluate the enrichment (2, 4, 6, 7 and 8 h) and elimination (2, 4, 6, 8, 10, 12, 14, 16, 18 and 20 d) of 2H and 18O (subcutaneously injected). The maximum enrichment was after 5 h (R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Another possible explanation for this finding is a potential lack of commitment by the owners, who could be giving extra food to the dogs and making weight loss more difficult (German et al, 2007; Hours et al, 2016). This possibility is a limitation of the study method, reinforcing the necessity of using better methodologies to assess the energy expenditure of domiciled dogs under weight loss programmes, such as the doubly labelled water method (Goloni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for this finding is a potential lack of commitment by the owners, who could be giving extra food to the dogs and making weight loss more difficult (German et al, 2007; Hours et al, 2016). This possibility is a limitation of the study method, reinforcing the necessity of using better methodologies to assess the energy expenditure of domiciled dogs under weight loss programmes, such as the doubly labelled water method (Goloni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To increase injection accuracy, the syringe was weighed empty, with the isotope solution, and again after solution injection (44) . Saliva samples were collected according to Goloni et al (24) , using hydrophilic cotton externally and adjacent to the mouth, next to the animal's lips. To enable this procedure, salivation was stimulated by placing one drop of sodium dipyrone (500 mg/ml, EMS) onto the cat's mouth, equivalent to 25 mg of dipyrone per cat.…”
Section: Isotope Application Evaluation and Calculation Proceduresmentioning
confidence: 99%
“…Caution was taken to prevent the cotton from absorbing moisture from the air before use by keeping it in sealed bags. All procedures, including isotope injection and saliva sampling, were validated in cats (24) . All saliva collections were performed by a trained veterinarian (C.G.…”
Section: Isotope Application Evaluation and Calculation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study [ 15 ] evaluated the relationships between oral sensory exposure and hormones involved in longer oral processing and how these relationships might have influenced satiation and food intake in humans [ 15 , 21 , 22 ]. It is well known that saliva contains information not only about the composition of the food, but also on the biological and physical properties where recently studies [ 23 , 24 ] reported saliva might be associated with body composition and energy expenditure, which were highly associated with satiety.…”
Section: Introductionmentioning
confidence: 99%